Speech by the Honourable Chief Minister, Penang, at the Closing of Baby Show Finals at the Dewan Sri Pinang on Sunday, 19th September, 1976 at 9.30 a.m. - Lim, Chong Eu (1976)
It gives me great pleasure to be present at the Baby Show Finals sponsored by the Penang Jaycees and Dutch Baby Milk Industries (M) Berhad.